2015
DOI: 10.1063/1.4907871
|View full text |Cite
|
Sign up to set email alerts
|

A parity-time symmetric coherent plasmonic absorber-amplifier

Abstract: Non-Hermitian parity-time (PT)-symmetric optical potentials have led to a new class of unidirectional photonic components based on the spatially symmetric and balanced inclusion of loss and gain. While most proposed and implemented PT-symmetric optical devices have wavelength-scale dimensions, no physical constraints preclude development of subwavelength PT-symmetric components. We theoretically demonstrate a nanoscale PT-symmetric, all-optical plasmonic modulator capable of phase-controlled amplification and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 46 publications
0
34
0
1
Order By: Relevance
“…The asymmetric forces can be understood from the fact that the system is not invariant under space inversion [38,39]. We use the wellknown PT phase-transition parameters, i.e., n 0 d=λ and n 00 =n 0 [35,[40][41][42], to conduct a detailed study concerning their influence on the optical forces, transmission, and eigenvalues of the scattering matrix:…”
Section: Theorymentioning
confidence: 99%
“…The asymmetric forces can be understood from the fact that the system is not invariant under space inversion [38,39]. We use the wellknown PT phase-transition parameters, i.e., n 0 d=λ and n 00 =n 0 [35,[40][41][42], to conduct a detailed study concerning their influence on the optical forces, transmission, and eigenvalues of the scattering matrix:…”
Section: Theorymentioning
confidence: 99%
“…Recently it has been shown that the light fields coupled to an optical cavity with an intra-cavity absorber can be completely absorbed and no light can escape through the cavity [3][4][5][6][7][8]. Such a cavity-absorber system acts as a coherent perfect absorber and may be useful for a variety of fundamental studies and practical applications [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…[42] where the author explore prospects of an experimental realization of CPA-laser action in a similar non-PT -symmetric system. …”
Section: Bilayermentioning
confidence: 99%
“…Figure 15 provides a graphical demonstration of this behavior. It shows the plots of u for the TE and TM modes of a PT -symmetric Nd:YAG two-slab system with the following Figure 11: (Color online) Graphs of u in units of u I (dashed navy curves) and | S | in units of | S I | (solid red curves) for the singular TE and TM modes of the constructive configuration of a PT -symmetric Nd:YAG two-slab system given by (42) and (43). Figure 12: (Color online) Graphs of the angle Θ between the Poynting vector S and positive z-axis for the TE and TM modes considered in Fig.…”
Section: Inclusion Of the Effects Of Dispersionmentioning
confidence: 99%